ENHANCING PRIMARY HEALTHCARE CAPACITY IN MULTIDISCIPLINARY MANAGEMENT OF CLEFT LIP AND PALATE: A PRE-POST INTERVENTION STUDY FROM THE CLEFT MONTH 2025 WEBINAR AND WORKSHOP IN JAKARTA, INDONESIA - Melinda Harini; Jenny Lauvita; Luh Karunia Wahyuni; Kristaninta Bangun; Prasetyanugraheni Kreshanti; Vika Tania; Widjajalaksmi Kusumaningsih; Nidya Yunaz; Tashiani Candra; Medha Paramitajati; Annisa Nurhasana; Amanda Yufika; Fally Usman Arif; Anindira Rustandi (Jurnal Rekonstruksi dan Estetik, 2026)
Highlights: Hybrid webinar–practical hands-on workshop training significantly improved primary healthcare providers’ competencies in cleft lip and palate detection, referral, and multidisciplinary management. Knowledge improvement occurred consistently across all professional backgrounds with no significant differences between occupations. Abstract: Introduction: Cleft lip and palate are the most common craniofacial anomalies in Indonesia, requiring early detection and comprehensive multidisciplinary management. Primary healthcare providers play a crucial role in early screening, family education, and timely referral, yet gaps in knowledge and skill persist. Methods: A pre-post intervention study was conducted during the Cleft Month 2025 Webinar and Workshop, organized by Cleft Craniofacial Center RSCM and the Department of Physical Medicine and Rehabilitation, Faculty of Medicine Universitas Indonesia, in collaboration with DKI Jakarta Health Office. Participants included doctors, nurses, and midwives from selected primary healthcare centers who voluntarily registered and attended the full program. Knowledge and skills in multidisciplinary cleft management were assessed using structured multiple-choice pre- and post-tests developed by subject experts, aligned with training objectives. Participant satisfaction was evaluated using a post-intervention questionnaire. Results: A total of 244 participants attended the webinar and 59 joined the hands-on workshop. Workshop participants (mean age 34 years) showed significant improvements in overall and topic-specific scores except for 4th topic about Physical Medicine and Rehabilitation: Feeding guidance for infants with cleft. Webinar participants (mean age 41 years) had a mean pre-test score of 61.3, with only 7% achieving ≥80. Post-test scores improved significantly across all sessions. No differences were observed across professions. Conclusion:The Cleft Month 2025 Webinar and Workshop effectively improved the knowledge and skills of primary healthcare providers in the multidisciplinary management of cleft lip and palate, supporting early detection and appropriate referral in Jakarta.